Back from the brink: retrieval of membrane proteins from terminal compartments - Seaman, MNJ (Wiley-Blackwell, 2019)
It has long been believed that membrane proteins present in degradative compartments such as endolysosomes or vacuoles would be destined for destruction. Now however, it appears that mechanisms and machinery exist in simple eukaryotes such as yeast and more complex organisms such as mammals that can rescue potentially ‘doomed’ membrane proteins by retrieving them from these ‘late’ compartments and recycling them back to the Golgi complex. In yeast, a sorting nexin dimer containing Snx4p can recognise and retrieve the Atg27p membrane protein whilst in mammals, the AP5 complex (with SPG11 and SPG15) directs the recycling of Golgi-localised proteins along with the cation-independent mannose 6-phosphate receptor (CIMPR). Although the respective machinery is different, there is much commonality between yeast and mammals regarding the mechanisms of retrieval and the physiological importance of these late recycling pathways.
Keywords: AP5 complex; Snx4p; lysosome; recycling; retrieval; vacuole; Adaptor Proteins, Vesicular Transport; Animals; Autophagy; Autophagy-Related Proteins; Carrier Proteins; Endosomes; Golgi Apparatus; Lysosomes; Mammals; Membrane Proteins; Protein Transport; Proteins; Receptor, IGF Type 2; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins; Sorting Nexins; Vacuoles